Meneropong Efektivitas dan Efisiensi Kabinet Koalisi Merah Putih Terhadap Tata Kelola Pemerintahan - Nurmala, Sheila Adi; Hadi, Candrika Pratisara (Legal Standing : Jurnal Ilmu Hukum, 2025)
This research explores the effectiveness and efficiency of the Red and White Coalition's Fat Cabinet under the leadership of President Prabowo Subianto, and its implications for state governance. Indonesia's presidential system, stipulated in the 1945 Constitution, gives the president the power to form a cabinet consisting of ministers appointed based on political considerations and competence. This research uses a qualitative method with a statutory and conceptual approach to analyze the structure and dynamics of the cabinet. The results show that although a fat cabinet has the potential to improve political stability and task specification, challenges such as inefficiency and coordination difficulties remain. Therefore, it is recommended that the Prabowo administration conduct periodic evaluations of ministry performance and increase transparency in decision-making to ensure policies that favor the public interest.